Thromboelastography characterized CD36 null subjects as slow clot formation and indicative of hypocoagulability - Lee, Bai-Chin; Lin, Kuan-Hsiao; Hu, Chung-Yi; Lo, Shyh-Chyi (Thrombosis research, 2019)
Platelet CD36 is the receptor for oxidized low-density lipoprotein and collagen. The conventional platelet test cannot distinguish CD36-null subjects from normal expression subjects. Thromboelastography (TEG) testing can analyze global hemostasis. TEG testing data on CD36-null subjects are not available. Our subjects were 40 apheresis platelet donors, including 8 CD36-null individuals. We grouped the donors according to the platelet CD36 expression levels to assess the effects of platelet CD36 expression levels on TEG measurement variables. The whole blood TEG test revealed that CD36-null subjects had prolonged reaction time of fibrin formation (TEG R time) and a slower rate to build up cross-linked fibrin (TEG α angle). The final maximal amplitudes of clot formation showed little difference between CD36-null individuals and normal expression individuals. Correlation analysis showed that CD36 expression levels were negatively correlated with TEG R time (r = −0.342, p = 0.031) and positively correlated with the TEG α angle (0.379, p = 0.016). TEG testing on apheresis platelet samples with diminished heterocellular interaction did not reveal differences between CD36-null and normal expression individuals. A subanalysis of the data of a group of healthy subjects showed that platelet CD36 levels correlated positively with platelet–monocyte aggregates (PMAs). Low PMA can diminish heterocellular interaction and likely explain the abnormal TEG results observed in CD36-null individuals. TEG distinguishes CD36-null subjects from normal CD36 expression subjects as having a slower rate of fibrin formation and reassessment of TEG-based diagnostic monitoring is necessary for CD36 null subjects.